Type and Duration of Use of Hormonal Contraceptives as a Trigger for Maternal Weight Increase in Family Planning Acceptors in Bali: A Cohort Study - Dewi, Ni Kadek Evi Komala; Wandia, I Made; Permatananda, Pande Ayu Naya Kasih (Jurnal Kesehatan Metro Sai Wawai, 2023)
Introduction: Hormonal contraceptives are widely chosen by mothers to regulate the number of children and the spacing of births. However, the use of hormonal contraceptives provokes the side effects of weight gain. Purpose: This study evaluated the relationship between the type and duration of hormonal contraceptive use with weight gain in family planning acceptance in the Community Public Health Ubud I sub-district of Bali Province, Indonesia. Methods: The cohort study is a retrospective research design. A total of 92 acceptors, namely mothers who use contraception for at least 6 months as samples. Data are secondary sourced from medical records at Community Health Centers that meet the research criteria. Questionnaire as a measuring tool to obtain data on the type and duration of contraceptive use and body weight before and after hormonal contraceptive use. Analysis of bivariate data using the chi-square test and Wilcoxon test. Results: The number of 92 study subjects after conducting uji Wilcoxon found an association between hormonal contraceptive use and weight gain (p = 0.001) and the chi-square test showed a relationship between the length of contraceptive use and weight gain (p = 0.001). Conclusion: Weight gain in mothers is influenced by the length of hormonal contraceptive use. The duration of use of hormonal-type contraceptives needs to be considered as the basis for the realization of a program to prevent weight gain in family planning acceptors. Latar Belakang: Kontrasepsi hormonal banyak dipilih ibu-ibu untuk mengatur jumlah anak dan jarak kelahiran anak. Namun, penggunaan kontrasepsi hormonal memicu efek samping peningkatan berat badan. Tujuan: untuk mengevaluasi efek antara jenis dan lama penggunaan kontrasepsi hormonal dengan peningkatan berat badan pada akseptor keluarga berencana di Pusat Kesehatan Masyarakat kecamatan Ubud I Provinsi Bali, Indonesia. Metode: Studi cohort merupakan desain penelitian bersifat retrospektif. Sebanyak 92 aksepor, yaitu ibu-ibu pengguna kontrasepsi minimal 6 bulan sebagai sampel. Data bersifat sekunder bersumber rekam medis di Pusat Kesehatan Masyarakat yang memenuhi kriteria penelitian. Kuesioner sebagai alat ukur untuk memperoleh data jenis dan lama penggunaan alat kontrasepsi dan berat badan sebelum dan sesudah penggunaan kontrasepsi hormonal. Analisis data bivariat menggunakan uji chi square dan uji Wilcoxon. Hasil: Subjek penelitian berjumlah 92 setelah dilakukan uji wilcoxon menemukan ada hubungan penggunaan kontrasepsi hormonal dengan peningkatan berat badan (p=0,001) dan uji chi square menunjukkan terdapat hubungan antara lama penggunaan kontrasepsi dengan peningkatan berat badan (p=0,001). Simpulan: Peningkatan berat badan pada ibu-ibu dipengaruhi oleh lama penggunaan kontrasepsi hormonal. Lama penggunaan kontrasepsi jenis hormonal perlu diperhatikan sebagai dasar perwujudan program pencegahan peningkatan berat badan pada akseptor keluarga berencana.